ANTHROPOMETRIC TYPOLOGIES OF CONSUMERS IN MODERN CLOTHING DESIGN - Головчанська, Є. О. (Art and Design, 2019)
Explore the existing anthropometric classifications of women’s figures from the point of view of the clothes’ design for industrial production. To reveal the methodological significance of anthropometric classifications of consumer figures in the development of structural construction and content of clothing collections of industrial production. For the purpose of structuring consumer typology as the basis for designing industrial production clothing were used following methods: analytical-typological, comparative-typological, comparative-historical and comparative methods. In the article are analyzed the existing anthropometric typologies of female figures in the context of generally accepted sewing industry classifications, as well as modern trends in the creation of harmonic images with using visual illusions. Also in the article are determined the basic types of women’s body forms, which are the most frequently meet. Accordingly, it is advisable to take into account these types of figures in the design of women’s clothing of industrial manufacture. The scientific novelty consists in systematizing modern typologies of the body shape of women for the design of clothing with their subsequent use in the process of designing an industrial collection of modern women’s clothing. The systematized information is given about the classification of the modern typology of female figures for the design of assortment collections of promising women’s clothing. The presented researches reveal ways of development and active use of methods of visual illusions for the development of women’s clothing of industrial production.